2004
DOI: 10.1210/en.2004-0067
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of an Unnamed Protein, RDA288, in the Mechanism through which Progesterone Mediates Its Antiapoptotic Action in Spontaneously Immortalized Granulosa Cells

Abstract: Progesterone (P4) inhibits apoptosis of rat granulosa cells and spontaneously immortalized granulosa cells (SIGCs), which were derived from rat granulosa cells. Defining the mechanism through which P4 mediates its action has been difficult because these cells do not express the classic nuclear P4 receptor. Previous studies have shown that a P4 receptor antibody, C-262, detects a 60-kDa protein that is involved in regulating P4's antiapoptotic action. Using a C-262 affinity column, this 60-kDa protein was isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 41 publications
3
40
0
Order By: Relevance
“…55,56 P4 also blocks apoptosis in lactating mammary glands 57 and supplementation of P4 following weaning can prevent regression of mammary tissue by attenuating epithelial cell death. 56 A number of studies involving both primary cells 58 and transformed cell lines 13 have demonstrated that P4 prevents cells from undergoing apoptosis during stress regardless of whether or not the cells express the classical PGR. Our findings here place PGRMC1 squarely in the middle of the pathway by which progestins promote survival of cancer cells derived from female reproductive tissues.…”
Section: Discussionmentioning
confidence: 99%
“…55,56 P4 also blocks apoptosis in lactating mammary glands 57 and supplementation of P4 following weaning can prevent regression of mammary tissue by attenuating epithelial cell death. 56 A number of studies involving both primary cells 58 and transformed cell lines 13 have demonstrated that P4 prevents cells from undergoing apoptosis during stress regardless of whether or not the cells express the classical PGR. Our findings here place PGRMC1 squarely in the middle of the pathway by which progestins promote survival of cancer cells derived from female reproductive tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Some examples of such nongenomic progesterone action include facilitation of female mouse sexual behavior (Frye & Vongher 1999), oocyte maturation in Xenopus (Masui & Markert 1971), and spotted sea trout (Zhu et al 2003b), as well as the acrosome reaction in sperm (Meizel & Turner 1991). Putative mPRs have been identified in tissues such as human sperm (Luconi et al 1998, rat brain (Krebs et al 2000), rat granulosa cells (Peluso et al 2004), porcine liver (Meyer et al 1996), human liver, kidney, and placenta (Meyer et al 1998). Members of the mPR family described in this study have previously been identified in fish oocytes (Zhu et al 2003b), fish sperm (Thomas et al 2005b), various human tissues (Zhu et al 2003a, Chapman et al 2006, Karteris et al 2006, Dressing & Thomas 2007, Nutu et al 2007, rat corpus luteum (Cai & Stocco 2005), and sheep ovary (Ashley et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…5; Table 2E). Rda288, also known as PAIRBP1 (Plasminogen activator inhibitor 1 RNA-binding protein or PAI-1 mRNA binding protein), is involved in mediating the antiapoptotic action of progesterone (P4) in spontaneously immortalized granulose cells (SIGCs) (Peluso et al, 2004). Its expression is also regulated by gonadotropins in granulose and luteal cells (Peluso et al, 2005).…”
Section: Pancreas Expressionmentioning
confidence: 99%